The COVID-19 pandemic and structural transformation in Africa: Evidence for action - Julia Leininger; Christoph Strupat; Yonas Adaye Adeto; Abebe Shimeles; Wilson Wasike; Mariya Aleksandrova; Axel Berger; Clara Brandi; Michael Brüntrup; Francesco Burchi; Eva Dick; Amirah El-Haddad; et al. (Deutsches Institut für Entwicklungspolitik (DIE), 2021)
This study analyses how strengths and weaknesses of economic, societal, political and environmental structures played out during the Covid-19 crisis in Africa since March 2020. Its main aim is to improve evidence on the direct and indirect effects of the pandemic on African countries and, based on that evidence, identify policy implications and formulate recommendations. It comprises the analysis of (a) direct impacts of the pandemic as well as of policy responses such as lockdowns and their potential determinants; (b) indirect effects of lockdowns and policy responses to the pandemic on economic, social, political and environmental domains in the light of structural strengths and weaknesses of African countries. In general, the study is based on the assumption that economic and other structures determine the magnitude and direction of the pandemic's impact on the short and long run. Its added value is the thematic comprehensiveness and the comparative analysis of country clusters. Amongst many other findings, the analysis shows the important role of social cohesion for coping with the pandemic and for sustainable development on the longer run. This implies the need for (a) material and immaterial investments in good and trustful relationships within societies and between society and the state; (b) incentives for increasing cooperation of individuals for a common good need to be at the core of future development strategies. It identifies a trias of political priorities, which are all equally important and relate to each other. They contain (a) inclusive and green economic development that must be linked to (b) the establishment and improvement of universal social systems (health, education, social protection in case of poverty, old age and unemployment) as well as (c) a redesign of political institutions that are capable and inclusive to collect revenues and provide public goods. (d) None of these policy priorities will be effective on the long run without saving ecosystems.
Keywords: 330